Air Layering in Galwang (Albizia lucida Benth.) a Lac Host Plant - Srivastava, S. C.; Kumar, P.; Mishra, Y. D. (Indian Forester, 1994)
An experiment conducted for propagation of Albizia lucida Benth. Through air layering has been described in this paper.